ANALISIS INOVASI PELAYANAN PEGAWAI MENGGUNAKAN APLIKASI SISTEM ELEKTRONIK LAYANAN ASN DAN INFORMASI SATU PINTU (SELAIS) DIKANTOR REGIONAL XII BADAN KEPEGAWAIAN NEGARA (BKN) PEKANBARU - Rehmalemna Tarigan; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The State Civil Service Agency (BKN) is one of the non-ministerial government agencies in Indonesia that has the task of carrying out government duties in the field of state personnel management. Therefore, the Regional Office XII of BKN Pekanbaru made an innovation in personnel services using the SELAIS application. SELAIS is an online application that supports a web-based integrated service center designed to facilitate staffing services for the XII BKN Pekanbaru regional office. The purpose of this study was to identify personnel service innovations using the SELAIS application and to determine the supporting and inhibiting factors in the implementation of SELAIS application innovations at the Regional Office XII BKN Pekanbaru. This study uses descriptive qualitative methods, the selection of informants using purposive sampling technique. Data collection techniques are through observation, interviews and documentation. The results showed that employee service innovation using the SELAIS application at the Regional Office XII of BKN Pekanbaru had been implemented well. The supporting factors in the application of the SELAIS application are motivation, infrastructure, and human resources. And the inhibiting factors in the application of the SELAIS application, namely, the socialization that has not been optimal and the lack of knowledge sharing between operators in the agency so that there are still employees who perform services manually because they do not know about the jams application to facilitate staffing services. Key word: Innovation, service, electronic-based service innovation